Foresight, Climate Change and Agrifood Systems - Thurlow, James; Hartley, Faaiqa (2023)
Thurlow, James; Hartley, Faaiqa, and others. 2023. Foresight, Climate Change and Agrifood Systems: IFPRI-CGIAR’s modeling of climate risks and impacts. PowerPoint presentation given during the AIM4C IFPRI site visit, Washington DC USA, May 9, 2023